Effect of exchange rate volatility on foreign direct investment - the case of Kenya - Waweru, Wanuma (Strathmore University, 2015)
The purpose of this research study was to examine the effect of exchange rate volatility on foreign direct investment (FDI) in a developing nation with the focus being Kenya. Time series data ranging from 1993-2013 were used with ARCH and GARCH models being utilized to determine the •volatility of tl1e exchange rate. The study showed that the volatility of the exchange rate has a negative impact on FDI and that the liberalization of the economy has not really contributed to greater FDI inflows to the country. Also revealed in the study was that stock FDI and political stability are likely to draw in more funds from foreign investors and that contrary to commonly held thought, per capita GDP does not really feature as a determinant in a foreign investor's decision process when deciding whether or not to invest in the Kenyan market.
Submitted in partial fulfillment of the requirements for the Bachelor of Business Science at Strathmore University
Keywords: Exchange rates; Volatility; Foreign direct investment